Global Contraceptive Failure Rates: Who Is Most at Risk?. Issue 1 (21st February 2019) - Bradley, Sarah E.K.; Polis, Chelsea B.; Bankole, Akinrinola; Croft, Trevor
Abstract: Contraceptive failure is a major contributor to unintended pregnancy worldwide. DHS retrospective calendars, which are the most widely used data source for estimating contraceptive failure in low‐income countries, vary in quality across countries and surveys. We identified surveys with the most reliable calendar data and analyzed 105, 322 episodes of contraceptive use from 15 DHSs conducted between 1992 and 2014. We estimate contraceptive method‐specific 12‐month failure rates. We also examined how failure rates vary by age, education, socioeconomic status, contraceptive intention, residence, and marital status using multilevel piecewise exponential hazard models. Our failure rate estimates are significantly lower than results from the United States and slightly higher than previous studies that included more DHS surveys, including some with lower‐quality data. We estimate age‐specific global contraceptive failure rates and find strong, consistent age patterns with the youngest users experiencing failure rates up to ten times higher than older women for certain methods. Failure also varies by socioeconomic status, with the poorest, and youngest, women at highest risk of experiencing unintended pregnancy due to failure.